Design of a flexible contact-mode piezoresistive detector for time-based high sensitivity acceleration sensing - Rajaraman, V. (2010)
This work reports on the design and modeling of a new flexible contact-mode 1-DOF piezoresistive contact-force and impacttime detector used for acceleration sensing in the time domain. The key advantages of the contact-mode detection mechanism are the use of simple readout circuitry, compactness, good linearity, scalability, and the potential to realize a higher precision accelerometer due to time-based measurement. Several detector designs are considered and based on their performance an I-shaped beam detector is chosen that meets the design criteria. The estimated mechanical and electrical parameters of I-shaped beam detector are presented.